Refugee - Williams, Sean, 1967- (Williams, Sean, 1967- Force heretic, 2003)
While Luke Skywalker and the Jedi continue their search for Zonama Sekot, a living planet that holds the key to defeating the Yuuzhan Vong, Han and Leia confront deception and treachery as they struggle to bring peace to a region of the galaxy that has descended into chaos.